PROCESSO DE PROJETO PARA A ELABORAÇÃO DE ESTRUTURAS DE SUPORTE PARA PAINÉIS FOTOVOLTAICOS - Gasparetto, Claudia; Latosinski, Karina; Yuba, Andrea; Pinto, João (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The installation of photovoltaic systems is an alternative way to provide energy in remote areas. This kind of system is complex and expensive but its installation is quite simple and does not constitute a good opportunity to interact with local communities. But these interactions could be a good chance to know the habits of the communities, aiming to create resilient systems. So, one of the strategies created by this project was the substitution of the aluminum racking system by a labor-intensive structure, made with bamboo., Based on the concepts of DSR and appropriate technology, this paper present the development of the new ground mounting system, based on a study case, in Jamaica. A 6 component based structure was developed, using simple tools and equipment. A prototype was built and tested for a whole year and the design had feedbacks to be improved. Its cost is around U$ 7.50 per panel, which is about 80% cheaper the the its aluminium version. The results will be applied in real conditions in Jamaica next 2018, July. The application will allow testing the labor-intensive strategy to aggregate local farmers in the construction process.